2017
DOI: 10.1186/s12889-016-3973-1
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of the metabolic syndrome in a farm worker community in the Boland district, South Africa

Abstract: BackgroundIn South Africa, not much is known about MetS in farm working communities. This study aimed to describe the prevalence of the MetS in a farm working population from the Boland winelands district of the Western Cape, South Africa.MethodsA cross-sectional study was followed among farm workers (aged 20–60 years) from surrounding wine estates. The questionnaires used described socio-demographic status, ethnic background, alcohol consumption, smoking, exercise and daily medication. Anthropometric assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 37 publications
2
16
1
Order By: Relevance
“…Age was significantly associated with LDL-C levels (r = 0.319, p = 0.002), WC (r = 0.452, p < 0.001), systolic (r = According to the American Heart Association (AHA) definition of MetS, the prevalence of MetS among the women in this study was 53.3%, which was higher than the 44.9% and 46.3% found among black urban women 25 and coloured women respectively in the Western Cape. 22 The most prominent MetS risk factors among the women in this study were low HDL-C and high serum TRG levels, followed by visceral obesity, which were consistent with another study conducted among black women, 25 but inconsistent with the results of the study among coloured women. 22 Reduced HDL-C and hypertriglyceridemia, the two main types of dyslipidaemia associated with MetS, 21 were also found in this study.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Age was significantly associated with LDL-C levels (r = 0.319, p = 0.002), WC (r = 0.452, p < 0.001), systolic (r = According to the American Heart Association (AHA) definition of MetS, the prevalence of MetS among the women in this study was 53.3%, which was higher than the 44.9% and 46.3% found among black urban women 25 and coloured women respectively in the Western Cape. 22 The most prominent MetS risk factors among the women in this study were low HDL-C and high serum TRG levels, followed by visceral obesity, which were consistent with another study conducted among black women, 25 but inconsistent with the results of the study among coloured women. 22 Reduced HDL-C and hypertriglyceridemia, the two main types of dyslipidaemia associated with MetS, 21 were also found in this study.…”
Section: Resultssupporting
confidence: 67%
“…22 The most prominent MetS risk factors among the women in this study were low HDL-C and high serum TRG levels, followed by visceral obesity, which were consistent with another study conducted among black women, 25 but inconsistent with the results of the study among coloured women. 22 Reduced HDL-C and hypertriglyceridemia, the two main types of dyslipidaemia associated with MetS, 21 were also found in this study. The prevalence of abnormally low HDL-C levels nationally at 47.9% 26 was much lower than the 78.7% found in this study at baseline.…”
Section: Resultssupporting
confidence: 67%
“…Muthunarayanan in India also reported the same finding [29]. According to a study finding from South Africa, MetS was highest among 40-49years old individuals and decrease thereafter [31]. Systematic review findings from Iran indicated that being older adults, and those with low physical activity have been reported to have a higher rate of MetS [38].…”
Section: Discussionmentioning
confidence: 77%
“…A study done by Anas Ahmad Sabir et al in Nigeria reported a high prevalence of MetS and its components using NCEP ATP III criteria with a prevalence of 35.1%, 56.1%, 46.1%, 32.7%, 28.0%, and 22.4% for MetS, low HDL-c, hypertension, dysglycemia, central obesity, and elevated triglyceride respectively[36]. A study conducted in South Africa among farmworkers also indicated the prevalence of the individual metabolic syndrome components as 64.9%, 56.4%, 56.4%, 31.9% and 23.4% for hypertension, abdominal obesity, low HDL cholesterol, elevated triglyceride level, and elevated fasting blood glucose respectively[31]. Abdominal obesity (53%), low HDL-c (34%), high triglyceride (21%) and hyperglycemia (20%) were the most frequently occurring risk factors for metabolic syndrome in the United Arab Emirates[37].Age is significantly associated with MetS in this study.…”
mentioning
confidence: 99%
“…This sub-study included n = 120 female farm workers between the ages of 20 and 60 years whom formed part of a larger farm worker study performed during 2015 [43]. During each site visit, experimental procedures were communicated with an opportunity to address any questions about the study.…”
Section: Study Populationmentioning
confidence: 99%